2019
DOI: 10.29392/joghr.3.e2019013
|View full text |Cite
|
Sign up to set email alerts
|

Women’s modern contraceptive use in sub-Saharan Africa: does men’s involvement matter?

Abstract: Back Background ground Men's involvement in family planning can play an important role in improving the use of modern contraceptives. Several studies have shown that family planning interventions that involve men have resulted in positive outcomes. However, these studies are mainly case-control studies with a specific focus area. This paper used data from men's responses in Demographic and Health Surveys (DHS) in 27 sub-Saharan African countries to study whether there is an association between men's involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Second, the overall high levels of intermediate behavioral determinants may be partially a function of social desirability bias, where some respondents may have responded more favorably than their actual opinions based on their expectations of what they think is the “correct” answer. Third, while this study examines partner communication, it does not factor in the importance of men’s actions or determinants, which have been shown to influence their wives’ health behaviors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the overall high levels of intermediate behavioral determinants may be partially a function of social desirability bias, where some respondents may have responded more favorably than their actual opinions based on their expectations of what they think is the “correct” answer. Third, while this study examines partner communication, it does not factor in the importance of men’s actions or determinants, which have been shown to influence their wives’ health behaviors [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the overall high levels of intermediate behavioral determinants may be partially a function of social desirability bias, where some respondents may have responded more favorably than their actual opinions based on their expectations of what they think is the "correct" answer. Third, while this study examines partner communication, it does not factor in the importance of men's actions or determinants, which have been shown to influence their wives' health behaviors [37,38]. Furthermore, while LCA is a rigorous statistical procedure, proper class assignment using this technique is not guaranteed and researchers can fall prey to "naming fallacy" where the class name does not accurately reflect class membership [39].…”
Section: Limitationsmentioning
confidence: 99%
“…Second, this study does not contain any measures of spousal communication or power dynamics, which have been the focus of other studies on women’s empowerment in Burundi [ 69 ]. Such factors are often the target of SBC interventions and are seen as one possible pathway that influences modern contraceptive use [ 23 , 27 , 46 , 70 ]. However, measures of spousal communication around family planning are not available in the 2016–17 Burundi DHS.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that male involvement in ANC is associated with benefits such as increased likelihood of adherence to HIV advice during pregnancy hence reduction of Mother to Child Transmission (MTCT) rates of HIV, improved utilization of maternal health services and reduced delays in the decision to seek health care (6)(7)(8)(9)(10).Despite its benefits, studies have also indicated that male involvement in ANC is affected by different individual, relational, institutional and societal related factors (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%